2022
DOI: 10.1016/j.jbc.2022.101655
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced phosphorylation of orthologues of the orphan receptor GPR35 functions as an activation sensor

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Mass spectrometry was performed at the University of Leicester Proteomics Facility. Samples were analyzed as described (40). Liquid chromatography/tandem mass spectrometry (LC-MS/MS) was carried out using an LTQ Orbitrap mass spectrometer (Thermo Fisher Scientific).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Mass spectrometry was performed at the University of Leicester Proteomics Facility. Samples were analyzed as described (40). Liquid chromatography/tandem mass spectrometry (LC-MS/MS) was carried out using an LTQ Orbitrap mass spectrometer (Thermo Fisher Scientific).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Besides coupling to heterotrimeric G proteins, GPR35 isoforms interact with -arrestin2, a process that depends on agonist-promoted phosphorylation of a species-conserved serine/threonine cluster in the receptor C-terminus (29). Following the profiling of G protein activation and signaling, we next investigated isoform-specific GPR35--arrestin interaction and receptor internalization.…”
Section: Ligand-induced Gpr35 Interaction With -Arrestinsmentioning
confidence: 99%
“…However, the use of selective small molecule GRK inhibitors, such as compound 101 to block GRK 2/3 [ 117 ] and compound 18 to block GRK5/6 [ 118 ], siRNA/shRNA methods [ 116 , 119 ] or CRISPR/Cas9 approaches targeting only a specific subset of relevant GRKs [ 107 , 120 ], is beginning to unravel the mysteries of these topics. In addition, the use of phospho-site-specific antibodies [ 16 , 121 , 122 ] and mass spectrometry analysis of the sites of regulated phosphorylation [ 16 , 96 , 122 , 123 ] are also providing valuable insights. For example, Marsango et al (2022) identified a crucial pair of threonine residues in the medium chain fatty acid receptor GPR84 that are only phosphorylated in response to receptor activation, and this occurs, at least in HEK293 cells, via GRK2/3 [ 16 ].…”
Section: Free Fatty Acid Receptormentioning
confidence: 99%
“…This regulation defines efficient interactions with arrestins and allows the separation of G protein-biased and more balanced GPR84 agonists [ 16 ]. Similarly, Divorty et al (2022) reported phospho-site-specific antisera that act as activation state-specific biomarkers for the orphan metabolite receptor GPR35 [ 122 ]. Here, pre-treatment with the GRK2/3 blocker compound 101 significantly decreased the agonist-induced phosphorylation of human, and particularly mouse, orthologues of GPR35, as detected by these antisera.…”
Section: Free Fatty Acid Receptormentioning
confidence: 99%